Pathway to Entrepreneurship University: An Autoethnography of Entrepreneurial Research Experience - Afifah Azizah; Juneman Abraham; Bay Dhowi (Intelektual Pustaka Media Utama, 2017)
Many universities in Indonesia are currently competing to become the best Entrepreneurship University. A number of theoretical models and public policies have been formulated at the national and local levels, and attempts targeting cognitive, affective, and psychomotor changes have been made. However, so far the emphasis on business orientation is still thick as if entrepreneurship deals only with the creation of economic benefits. In addition, evaluation at the micro level appears to be rarely performed. This research uses qualitative approach with autoethnography method. The purpose of this study is to explore the experience of entrepreneurial activity in the research track in Bina Nusantara University, Indonesia. This study shows the acquisition of a number of key competencies of entrepreneurship, mainly from the viewpoint of the first person (the actor/participant, the first author), together with the research supervisor (second author) and faculty supervisor (third author). The experience is further reflected theoretically in the Discussion section of this article. The unique feature of this autoethnography is the depiction of innovative learning gained from the concrete process of falling and awake for a semester passed by the participant. There are appreciations of diversity of opportunities or channels, of the role of historicity of the self, narrative process, and altruism driving force. This study results might be useful for sharpening entrepreneurship program and curriculum especially in universities that make entrepreneurship an orientation of students and graduates that is inevitable nowadays.